8th Industrial Fluid Properties Simulation Challenge: n-Perfluorohexane adsorption prediction on activated carbon BAM-P109 by molecular simulation. Issue 1 (February 2016) - Gonciaruk, Aleksandra; Runcieman, Louis; Avendaño, Carlos; Siperstein, Flor R
We combine two approaches to describe an activated carbon which contains micro- and mesopores. We propose a simple approach of packing individual three-dimensional rigid structures to represent microporous region of commercially available BAM-P109 activated carbon. Mesopores are represented by planar walls interacting via the standard Steele 10-4-3 potential assuming experimental pore-size distribution. The models are used to predict n -perfluorohexane adsorption at 273 K temperature. We used uncharged united atom model for n -perfluorohexane molecule. The non-bonded interactions were described by the Gordon potential model, with parameters adjusted to reproduce the Mie force field potential, which was designed to accurately represent vapour pressure of alkanes and perfluoroalkanes. Adsorption isotherm was calculated using Grand Canonical Monte Carlo method implemented in MCCCS Towhee. We show that predicted n -perfluorohexane loading at relative pressures of interest are significantly lower than the experimental ones. The underprediction is attributed to the low aromatic carbon interaction strength and sensitive calculations of chemical potential. Adjusted interaction parameter of aromatic carbon and chemical potential led to n -perfluorohexane adsorption that agreed well with the reported experimental values.